Endodontic Treatment of an Upper Lateral Incisor with Oehlers’ Type II Dens Invaginatus: A Case Report - Mesquita-Júnior, Ary Alves; dos Santos , Suelem Brenda; Reis, Rebeka de Oliveira; Cunha, Ingrid Luiza Mendonça; Hanan, Aida Renée Assayag; Sponchiado Júnior, Emílio Carlos (Iranian Endodontic Journal, 2025)
Dens invaginatus is a developmental malformation that is caused by the invagination of the enamel organ into the internal region of the dental papilla before tissue calcification. The aim of the present report is to discuss a clinical case of endodontic treatment of tooth #12, using bioceramic sealer. The extraoral examination revealed atypical anatomy, while vitality and percussion tests were negative, palpation test was positive. Edema was observed in the adjacent gingival mucosa. Based on clinical and tomographic findings, the diagnosis was pulp necrosis with chronic periapical abscess and Oehlers’ type II dens invaginatus. In the first session, access surgery was performed with spherical drills with the aid of an operating microscope (OM) and an ultrasonic diamond tip. Four canals were located, and they were partially debrided and medicated. In the second session, odontometry and chemical-mechanical preparation with nickel-titanium instruments were performed. The irrigation solution was 2.5% sodium hypochlorite. The root canals were filled with calcium hydroxide paste and the chamber was temporarily sealed. During the third session, ultrasonic irrigation was applied for final washing and the root canals were filled with Bio-C sealer using the classic single-cone technique. At 6-month follow-up, the tooth was asymptomatic and the radiography revealed significant bone repair. It was concluded that tomography, operating microscope, ultrasonic irrigation, and materials with greater flow, such as bioceramic sealers, enhanced the clinical success of the clinical case.